ҮШИНШИ РЕНЕССАНС ШАРАЯТЫНДА «ҮЗЛИКСИЗ РУЎҲЫЙ ТӘРБИЯ» КОНЦЕПЦИЯСЫН ӘМЕЛГЕ АСЫРЫЎ МАЗМУНЫ - Бозорова, М.Қ. (FAN va JAMIYAT, 2023)
This article deals with the implementation of the concept of "Continuing spiritual education" in the conditions of the third renaissance, the ongoing work on the scientific and technical reform of youth education in the conditions of the new renaissance on a modern basis, based on the needs of today, is presented in the form of evidence-based basic competencies.